A Moral Technology : Electrification as Political Ritual in New Delhi - Coleman, Leo (Book collections on Project MUSE., 2017)
"This book is about the cultural politics of electrification in India's capital city, and the role of technological infrastructures in shaping contemporary political imaginations in India--imaginations of the state, and also at a local level, of urban interdependence and solidarity. Drawing on both historical and ethnographic case-studies, this book examines colonial electrical installations in Delhi, nationalist legislation for nationwide electrification, and electricity privatization and neighborhood political organization in the early 2000s"--